A systematic review of N-of-1 trials and single case experimental designs in physiotherapy for musculoskeletal conditions. (December 2022) - Nikles, J.; Evans, K.; Hams, A.; Sterling, M.
Abstract: Background: Single Case Experimental Designs (SCEDs) are especially useful for small heterogeneous samples. Their role in evaluation of physiotherapy interventions for musculoskeletal conditions has not been systematically reviewed. Objectives: Systematically review use, purpose, and outcomes of SCEDs for physiotherapy interventions for musculoskeletal conditions. Data sources: Electronic databases and grey literature, searched using pre-defined terms. Study selection or eligibility criteria: Studies of human participants enrolled in eligible SCEDs (individual or a series). Study appraisal and synthesis methods: We extracted study characteristics, analytic methods and results, synthesising these descriptively. We used RoBiN-T scale to assess risk of bias. Results: We included 19 SCEDs comprising 92 participants, with wide variability in design, methodology, analysis and in conditions and interventions evaluated. 95% of participants responded favourably to the tested intervention. Overall risk of bias was high, due to poor internal validity, especially regarding randomisation, blinding, inter-rater agreement and measurement of treatment adherence. Visual analysis alone was performed in 55% of studies. Assessment of provider and participant satisfaction was limited. Conclusions and implications: of key findings : SCEDs may be well-suited to evaluation of physiotherapy interventions for musculoskeletal conditions, but the risk of bias in studies to date is high. Following SCED guidelines to minimize the risk of bias and maximise clinical usefulness is recommended. Highlights: Key messages of the article/what the paper adds to the current literature. SCEDs may be well-suited to study physiotherapy for musculoskeletal conditions. More standardised and rigorous design, execution, analysis and reporting are needed. What new knowledge is added by this study. This is the first systematic review of SCEDs in this field. The rigor of SCEDs in this field could be improved.